MONITORING AND CONTROL SYSTEM OF IOT-BASED GAS LEAK DETECTION - Muliawati, Fithri; Mustopa, Opa (JuTEkS (Jurnal Teknik Elektro dan Sains), 2020)
LPG gas leaks are one of the factors causing fires in housing, this is due to gas leaks not being able to be detected from the start because the gas content is usually small and not smellable, when there is a lot of gas outside the cylinder and there is a trigger or sparks around it, the fire does not occur. it is undeniable that it will happen. So that this can be avoided, a monitoring and control system for IOT-based Gas Leak Detection is created, by detecting lpg gas leaks by operating the MQ-06 sensor reading which has been set at a set point of 1960 ppm, with a maximum sensor reading limit of 10,000 ppm based on Arduino nano 10 bit with information transmission media in the form of the NodeMcu V3 module. The results of the MQ-06 sensor readings are processed in the Arduino program so that information is generated in the form of sound notifications generated by the buzzer, when the MQ-06 sensor detects LPG gas at a set point of 1960 ppm the sensor will send data in the form of an analog voltage sent to Arduino and converted into a digital voltage through the ADC facility to then send information, the sensor will send data to Arduino to be managed in the Arduino IDE software so that it can respond in the form of a buzzer as an alarm, displays information on the LCD and activates the exhaust fan, and this tool can also send information gas analog data to android smartphones using the Blynk platform via the internet network